2007
DOI: 10.1021/bc0602782
|View full text |Cite
|
Sign up to set email alerts
|

Protein−Liposome Conjugates Using Cysteine-Lipids And Native Chemical Ligation

Abstract: Liposomes have become popular drug delivery vehicles and have more recently also been applied as contrast agents for molecular imaging. Most current methods for functionalization of liposomes with targeting proteins rely on reactions of amine or thiol groups at the protein exterior, which generally result in nonspecific conjugation at multiple sites on the protein. In this study, we present native chemical ligation (NCL) as a general method to covalently couple recombinant proteins in a highly specific and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 36 publications
2
66
0
2
Order By: Relevance
“…Using a protein determination the amount of coupled protein was determined to be 1.58 nmol of CNA35 per 1 mmol lipid. Assuming a surface area of 0.6 nm 2 per lipid and unilaminar liposomes with a diameter of 200 nm (circa 420,000 lipids per liposome), approximately 660 copies of CNA35 were estimated to be present per liposome (33). A ratio of 1 CNA35 to 15 Mal-PEG2000-DSPE molecules was used, which would correspond to 700 proteins per liposome, therefore the coupling efficiency was around 95%.…”
Section: Introductionmentioning
confidence: 99%
“…Using a protein determination the amount of coupled protein was determined to be 1.58 nmol of CNA35 per 1 mmol lipid. Assuming a surface area of 0.6 nm 2 per lipid and unilaminar liposomes with a diameter of 200 nm (circa 420,000 lipids per liposome), approximately 660 copies of CNA35 were estimated to be present per liposome (33). A ratio of 1 CNA35 to 15 Mal-PEG2000-DSPE molecules was used, which would correspond to 700 proteins per liposome, therefore the coupling efficiency was around 95%.…”
Section: Introductionmentioning
confidence: 99%
“…104,105 The native chemical ligation (NCL) method 106,107 was employed successfully to create covalent linkages between recombinant proteins and the PEG-conjugated vesicles and micelles; NCL exclusively occurs at the protein C-terminus -often not involved in any binding activities with high specificity. These examples ( Figure 12) demonstrate a highly effective instillation of multiple functionalities (i.e., multiple collagen binding sites) into soft nanoparticles that may be necessary for targeting sites with multivalent architectures.…”
Section: In Vitro Binding Affinity Control Via Native Chemical Ligationmentioning
confidence: 99%
“…Recently, it was also reported that liposomes consisting of hepatitis B surface antigen and fluorescently labeled polystyrene beads or plasmids were used for tissue and cellular targeting with high specificity [88]. Another method of liposome ligation was reported by Reulen et al [89], which showed fluorescent proteins covalently coupled to cysteinefunctionalized phospholipids on the liposome surface for optical imaging of collagen.…”
Section: Optical Imaging With Liposome-based Nanoprobesmentioning
confidence: 99%